Analisis Pendidikan: Kebijakan Pendidikan Perspektif Nasional dan Madrasah - Ita Rosyada; Fitriyani Sanuhung; Mira Ifta Rimadhani; Muhammad Alwan Hakim (STAI Bumi Silampari, 2021)
Education is one of the supports for a country to progress, with a good and quality education system that will be able to describe how the government system works or the development of a country. In education, there are several things that need to be considered, among others, namely education policy. The education policy is made by the government to be implemented by all parties in education, be it teachers, students and school staff and employees. The purpose of forming educational policies is to meet the needs of students, educational policies are made through surveys of students and the course of education itself.